3D-Printed seed planter and well array for high-throughput seed germination screening. Issue 1 (13th December 2017) - Chai, Hui Hui; Lu, Yao; Fang, Can; Li, Ya Dan; Kang, Yue Jun; Li, Chang Ming; Yu, Ling
Abstract : A 3D-printed miniaturized well array and seed planter have been developed for in-field studies of seed quality and screening of conditions for seedlings. Abstract : Seed germination is an important means of evaluating seed quality. In the present study, a well array for a seed germination experiment was designed and fabricated by 3D printing for the first time. Each hollow cone-shaped well can hold one seed, which not only prevented the seed from falling out of the well but also ensured that part of the seed was fully exposed to the sublayer of wet filter paper, allowing it to receive water for germination. Coupled with a 3D-printed seed planter, single seeds can be quickly placed into arrayed wells. Moreover, the number of sprouts could be automatically obtained from image analysis, which greatly improved the efficiency of the entire experiment. In summary, the high-throughput, easy-to-use seed germination well array that we have developed has been shown to have potential applications in botanical seed research and agricultural production.